2012
DOI: 10.1142/s2010269012500135
|View full text |Cite
|
Sign up to set email alerts
|

About a Revolution: The Economic Motivations of the Arab Spring

Abstract: The paper reviews the economic motivations of the Arab Spring. After examining the possible relationships between the Arab riots and the global economic crisis started in 2007, the analysis focuses on some structural aspects characterizing North Africa and Middle East Countries, such as their demographic structure, the profound social inequalities and the discrepancy between the education levels, of youth in particular, and the civil and political rights accorded to the populations. The combination of youth de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 42 publications
0
31
0
2
Order By: Relevance
“…Moreover, a number of authors [e.g. 11,12] examined the economic motivations for the Arab spring and all found that the high unemployment rates and the high educational levels has led to the uprisings. Finally, some authors identified the positive influence of social media on the Arab spring revolts [e.g.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a number of authors [e.g. 11,12] examined the economic motivations for the Arab spring and all found that the high unemployment rates and the high educational levels has led to the uprisings. Finally, some authors identified the positive influence of social media on the Arab spring revolts [e.g.…”
Section: Reviewmentioning
confidence: 99%
“…Consequently, as seen by the previous summary, the main focus of research after the Arab spring was either on the motivations and the financial implications on Arab countries [e.g. 11,12], or on its political and economical implications for the west [e.g. 16,19].…”
Section: Reviewmentioning
confidence: 99%
“…At the same time, however, the poverty gap in the MENA region is relatively low when compared to other regions (on the level of developing countries) ranging between 1.64 per cent in 1981 and 0.35 per cent in 2011 (Fig. ) (Achcar , p.21; Ansani and Daniele ; Ncube et al . , p.4) .…”
Section: Manifestations Of Inequality: the Case Of The Arab Regionmentioning
confidence: 98%
“…Rather, inequality is on the rise and the state has reduced its public welfare role leaving people vulnerable to the brutality of the market. The Middle East and North African (MENA) region as a whole is far from being economically homogenous, where countries lie in different spectra in both their levels of economic development and their economic structures (Ansani and Daniele , p.3). Having one of the fastest growing populations in the world with an estimated 355 million in 2011, the MENA region has vast natural reserves of oil and natural gas that puts its known oil reserves at 50 per cent of the global total and (its known) gas reserves at an estimated 40 per cent of the global total (according to 2011 estimates) (Ncube et al .…”
Section: Manifestations Of Inequality: the Case Of The Arab Regionmentioning
confidence: 99%
“…For all the economic benefits of this shift the private sector failed to generate the sufficient number of employment opportunities that state and public sector institutions had previously provided (no matter how inefficiently), especially for young people. Analysts attribute this failure primarily to misguided policies-often uneven, hesitant and incomplete-and to weak institutional performance characterised by cronyism and corruption (Ansani and Daniele, 2012). 5 Whatever the causes of faltering Arab growth, in the period 2005-2010 Arab youth unemployment reached high levels averaging more than 25 per cent and it continued to rise in both 2011 and 2012 (the highest rate among various developing regions.…”
Section: On the Unravelling Of Autocracy In A Few Arab Countriesmentioning
confidence: 99%